A dual-FRET-based fluorescence probe for the sequential detection of MMP-2 and caspase-31. Issue 77 (4th October 2015) - Li, Shi-Ying; Liu, Li-Han; Cheng, Hong; Li, Bin; Qiu, Wen-Xiu; Zhang, Xian-Zheng
<x xml:space="preserve">Abstract</x> A novel turn-on fluorescence probe based on dual-FRET quenching processes was developed for the sequential detection of MMP-2 and caspase-3.